1956
DOI: 10.1002/cber.19560890717
|View full text |Cite
|
Sign up to set email alerts
|

Zur Kenntnis der Waldenschen Umkehrung VI: cis‐und trans‐1‐Methyl‐2‐amino‐cyclopentan und Salpetrige Säure

Abstract: cis-1 -Methyl-2-amino-cyclopentan gibt mit Salpctriger Siiure unter vorzugsweiser Erhaltung der Konfiguration 1 -Methyl-cyclo-pentanoL(2) 70:30, auDerdeni 1-Methyl-cyclopenten, A': A2 etwa 1 : 1. trow-1-Methyl-2-amino-cyclopentan gibt zur Biilfte Waldensche IJni kchrung, daneben nur 1-Methyl-Akyclopentcn. Das Cycloolefin niacht beim cis-Amin 23 yo, beim trans-Amin 35 yo des Reaktionsproduktes auB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1957
1957
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…[31] Rylander, while studying the reaction between 2-methyl-and 4-methylcyclohexanone with NH 3 , observed that a methyl group at the 2-position offers more steric hindrance to the formation of the secondary amine (Table 1). [32] Another interesting example of the influence of the steric hindrance of the starting compounds is found in the reductive amination of straight-chain aliphatic aldehydes, such as acetaldehyde, propionaldehyde and n-butyraldehyde, with glycine, which merely yields the corresponding secondary amines.…”
Section: Reviewsmentioning
confidence: 99%
“…[31] Rylander, while studying the reaction between 2-methyl-and 4-methylcyclohexanone with NH 3 , observed that a methyl group at the 2-position offers more steric hindrance to the formation of the secondary amine (Table 1). [32] Another interesting example of the influence of the steric hindrance of the starting compounds is found in the reductive amination of straight-chain aliphatic aldehydes, such as acetaldehyde, propionaldehyde and n-butyraldehyde, with glycine, which merely yields the corresponding secondary amines.…”
Section: Reviewsmentioning
confidence: 99%
“…[31] Rylander, while studying the reaction between 2methyl-and 4-methylcyclohexanone with NH 3 , observed that a methyl group at the 2-position offers more steric hindrance to the formation of the secondary amine (Table 1). [31] Rylander, while studying the reaction between 2methyl-and 4-methylcyclohexanone with NH 3 , observed that a methyl group at the 2-position offers more steric hindrance to the formation of the secondary amine (Table 1).…”
Section: Reviewsmentioning
confidence: 99%